2020
DOI: 10.3390/ijms21103720
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage Regulates Senescence-Associated Extracellular Vesicle Release via the Ceramide Pathway to Prevent Excessive Inflammatory Responses

Abstract: DNA damage, caused by various oncogenic stresses, can induce cell death or cellular senescence as an important tumor suppressor mechanism. Senescent cells display the features of a senescence-associated secretory phenotype (SASP), secreting inflammatory proteins into surrounding tissues, and contributing to various age-related pathologies. In addition to this inflammatory protein secretion, the release of extracellular vesicles (EVs) is also upregulated in senescent cells. However, the molecular mechanism unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 73 publications
0
39
0
Order By: Relevance
“…Changes in N-SMase levels have been reported in aging tissues [ 137 ]. A recent study has suggested that upregulation of N-SMase and ceramide biosynthesis contributed to the production of extracellular vesicles and prevented excessive inflammatory response [ 138 ]. However, the exact mechanism of how N-SMase activity contributes to senescence, whether it affects membrane dynamics or generates ceramides at certain membrane locales, is not known and is likely to be tissue specific.…”
Section: Various Lipid Classes Have Been Linked To Senescencementioning
confidence: 99%
“…Changes in N-SMase levels have been reported in aging tissues [ 137 ]. A recent study has suggested that upregulation of N-SMase and ceramide biosynthesis contributed to the production of extracellular vesicles and prevented excessive inflammatory response [ 138 ]. However, the exact mechanism of how N-SMase activity contributes to senescence, whether it affects membrane dynamics or generates ceramides at certain membrane locales, is not known and is likely to be tissue specific.…”
Section: Various Lipid Classes Have Been Linked To Senescencementioning
confidence: 99%
“…It was previously reported that SASP triggers senescence of the surrounding normal cells (51,52). Many studies have focused on these secreted factors and their proposed mechanism in bone metabolism (12,53).…”
Section: Discussionmentioning
confidence: 99%
“… 254 Oxidative stress induces DNA damage, which in turn activates the ceramide synthesis pathway leading to an increase in senescence-associated EV (SA-EV) biogenesis. 107 Latent membrane protein 1 (LMP1) is a viral protein that contributes to the modification of EV content and remodeling of the tumor microenvironment. LMP1 enhances EV production by utilizing LMP1-interacting proteins, including Hrs, Syntenin-1, and the ESCRT-III complex.…”
Section: Promotion Of Evs Releasementioning
confidence: 99%
“…105 Leptin regulates the mechanisms of biogenesis and release of exosomes and also increased the number of MVBs and release of MVBs in the cytoplasm of breast cancer cells. 106 Hitomi et al reported that DNA damage activates the ceramide synthetic pathway leading to an increase in senescence-associated EVs (SA-EV) biogenesis 107 The EVs biogenesis pathway, which is associated with the autophagy-mediated degradation pathway, leads to inhibition of apoptosis. The SA-EV pathway may play a significant role in cellular homeostasis, particularly in senescent cells.…”
mentioning
confidence: 99%